1981
DOI: 10.1007/bf00410666
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the tumorigenic response to benzo(a)pyrene in aqueous caffeine solution applied orally to Sprague-Dawley rats

Abstract: In a lifetime experiment benzo(a)pyrene (B(a)P) was administered to Sprague-Dawley rats either as an admixture to the diet or by gavage in an aqueous 1.5% caffeine solution. Dissolved benzo(a)pyrene induced more tumors of the forestomach than undissolved benzo(a)pyrene. The 1.5% caffeine solution (annual dose 27 g/kg) did not exert any carcinogenic activity under the conditions of this bioassay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Systemic administration produces mammary tumors; esophageal and forestomach tumors are produced by intragastric or oral administration (14)(15)(16)(17). Subcutaneous administration of BaP produces both site of injection fibrosarcomas and mammary tumors; intratracheal instillation and lung implantation both produced lung tumors (18)(19)(20)(21)(22) not been as widely studied in the rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration produces mammary tumors; esophageal and forestomach tumors are produced by intragastric or oral administration (14)(15)(16)(17). Subcutaneous administration of BaP produces both site of injection fibrosarcomas and mammary tumors; intratracheal instillation and lung implantation both produced lung tumors (18)(19)(20)(21)(22) not been as widely studied in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…Two solvent systems were routinely employed. System 1 was Dl = 1 M sodium phosphate, pH 6.0, with overnight chromatography onto a 5-cm Whatman grade 17 Chr wick, followed by a wash with water; D3 = 3.5 M lithium formate, 7 M urea, pH 3.5, with development 6-8 cm onto a Whatman-grade 1 wick, followed by a wash with water, a wash with 20 Mm This base, and an additional wash with water; D4 = 1:1 isopropanol:4 N ammonia, with development 6-8 cm onto a Whatmangrade 1 wick; and D5 = 1.7 M sodium phosphate, pH 6.8, with development 6 cm onto a Whatman-grade 1 wick. System 2 was Dl = 1 M sodium phosphate, pH 6.0, with overnight development onto a 10-cm Whatman-grade 3MM Chr wick followed by a wash with water; D2 = 2.75 M ammonium formate, developed 1 cm; D3 = 4.5 M lithium formate, 7 M urea, pH 3.5, followed by a wash with water; D4 prewash = 1 cm development with 0.5M Tris-HCl; D4 = 1.1 M lithium chloride, 0.5 M Tris-HCl, 7 M urea, pH 8.0, followed by a wash with water; and D5 = 1.0 M MgCl2, with development onto a 3-cm Whatman-grade 3MM Chr wick, followed by a final wash with water.…”
Section: Methodsmentioning
confidence: 99%
“…In a lifespan study of Sprague-Dawley rats fed diets that contained benzo [a]pyrene at levels that resulted in total doses of 0, 6 or 39 mg/kg bw per year, a slightly higher incidence of forestomach papillomas was observed in high-dose animals (10/64 versus 3/64 controls; p <0.1) (Brune et al, 1981). The incidence and total number of mammary gland tumours (fibroadenomas, adenomas and adenocarcinomas) were markedly increased in female CD rats treated with benzo [a]pyrene (50 µmol [13.21 mg]) by gavage once a week for 8 weeks followed by an observation period of 41 weeks .…”
Section: Ratmentioning
confidence: 99%
“…In two of these studies (Takayama and Kuwabara, 1982;Moh et al, 1984), no significant difference in the incidence of tumours at any site was found. The other three studies (Yamagami et al, 1983;Johansson, 1981;Brune et al, 1981) were found to be inadequate for evaluation (IARC, 1991). All studies on oral and intraperitoneal administration of caffeine to mice were found inadequate for evaluation.…”
Section: Studies In Experimental Animalsmentioning
confidence: 99%